Corporate governance, excess-cash and firm value: Evidence from ASEAN-5 - Akhtar, Tahir (Economics and Business Review, 2022)
This study investigates the role of the country- and firm-level governance practices on the relationship between excess-cash and firm value in ASEAN-5 markets. Using the Generalized Method of Moment models and a sample of 578 firms from 2010 to 2020 the study finds that excess-cash reduces firm value, indicating high agency costs and low firm value. However, excess-cash motivated by managerial ownership, founder CEO, board independence, shareholder rights and creditor rights increase firm value while excess-cash due to managerial entrenchment and CEODuality reduce firm value. In the sub-sample analyses the study finds that entrenched managers and board size play a less effective role in wasting excess-cash in low-excess-cash firms while independent directors play a higher monitoring role in high-excess-cash firms. In addition, governance at the country-level is more effective than at the firm-level in improving the value of excess-cash in large firms. The study offers unique evidence on the relationship between excess-cash and firm value by integrating corporate governance practices at the firm- and country-levels. The research aids practitioners, academics, policymakers and investors in developing the best liquidity policies to enhance business performance.